Comparison principle for linear non-cooperative elliptic systems - Boyadzhiev, G. (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2009)
This paper presents some sufficient conditions for the validity of the comparison principle for the weak solutions of non - cooperative weakly coupled systems of elliptic second-order PDE.